Therapeutic Potential of MSC-conditioned Medium: A Multifactorial Approach to Enhance Wound Healing - Anbiyaiee, Amir; Azizidoost, Shirin; Farzaneh, Maryam (Current Signal Transduction Therapy, 2024)
Wound healing is a highly intricate process that involves a coordinated interplay of various cellular and molecular events. In recent years, mesenchymal stem cells (MSCs) have garnered significant attention as a promising therapeutic modality due to their remarkable regenerative properties. In addition to their capacity for direct tissue repair and differentiation, MSCs release a diverse repertoire of bioactive factors into the surrounding microenvironment, collectively termed an MSC-conditioned Medium (MSC-CM). This review aims to elucidate the therapeutic potential of MSC-CM as a multifactorial approach to enhance wound healing. MSCCM encompasses an extensive range of factors, including growth factors, cytokines, chemokines, extracellular matrix proteins, and non-coding RNAs, which collectively orchestrate and stimulate multiple cellular processes crucial for effective wound healing. Notably, these factors play pivotal roles in promoting angiogenesis, stimulating the proliferation and migration of various cell types involved in wound repair, modulating the immune response, and facilitating extracellular matrix remodeling. Moreover, compelling evidence from preclinical and clinical studies demonstrates that MSC-CM administration accelerates wound closure, enhances reepithelialization, and improves the quality of granulation tissue. By harnessing the therapeutic potential of MSC-CM, we can pave the way for significant advancements in wound care, ultimately leading to improved patient outcomes.
Keywords: chemokines